The early development of new establishments: An evaluation of the role of spatial selection and agglomeration - Javier Changoluisa (Friedrich Schiller University Jena, 2021)
This paper analyzes the early development of new establishments evaluating the role of spatial selection and agglomeration. The analysis shows a clear and strong selection of more productive new establishments into larger regions, regardless of the foundation type. While at the end of the time-period analyzed new establishments located in larger regions still show higher productivity levels as compared to those located in smaller regions, the role of an agglomeration is very distinct depending on the foundation type. Spin-offs in larger regions tend to keep the higher productivity level shown in the first time period, but start-ups suffer negative agglomeration effects over time.
Keywords: L26; L25; R30; R12; 330; Entrepreneurship; agglomeration; firm selection; productivity